PENDIDIKAN MASYARAKAT DAN STRATIFIKASI SOSIAL DALAM PRESPEKTIF ISLAM - Abdullah Chozin; Taufan Adi Prasetyo (Institut Islam Mamba'ul 'Ulum Surakarta, 2021)
In people's lives there are often various kinds of hierarchical differences, ranging from differences in economics, politics, religion, race, geographical conditions, and even differences in education levels which often lead to more acute disparities and levels of social interaction in society. One of the main sources of social stratification is education. As it should be, education that has clear and potential functions and goals can make students mature, or recognize themselves and education should be a tool to improve the social status of the community, not the other way around.